2022
DOI: 10.1186/s12968-022-00851-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of global and segmental myocardial strain using cine DENSE at 3 T: a multicenter cardiovascular magnetic resonance study in healthy subjects and patients with heart disease

Abstract: Background While multiple cardiovascular magnetic resonance (CMR) methods provide excellent reproducibility of global circumferential and global longitudinal strain, achieving highly reproducible segmental strain is more challenging. Previous single-center studies have demonstrated excellent reproducibility of displacement encoding with stimulated echoes (DENSE) segmental circumferential strain. The present study evaluated the reproducibility of DENSE for measurement of whole-slice or global ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…The greatest existing hurdle to widespread adoption of strain CMR is repeatability. Although high reproducibility of global strain measurements has been demonstrated for different types of strain CMR approaches ( 74 76 ), reproducibility for more difficult segmental strain analysis is just emerging ( 77 ). If vendors can come to a consensus and provide standardized, reproducible strain CMR platforms, multiple diagnostic opportunities will emerge.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest existing hurdle to widespread adoption of strain CMR is repeatability. Although high reproducibility of global strain measurements has been demonstrated for different types of strain CMR approaches ( 74 76 ), reproducibility for more difficult segmental strain analysis is just emerging ( 77 ). If vendors can come to a consensus and provide standardized, reproducible strain CMR platforms, multiple diagnostic opportunities will emerge.…”
Section: Discussionmentioning
confidence: 99%
“…There are two types of respiratory motion: (1) that which changes the heart's position before displacement encoding, Δr R 1 , and that which occurs between displacement encoding (DE) and readout (RO), Δr R 2 . Δr R 1 leads to a position shift of the magnetization amplitude, whereas Δr R 2 gets encoded into the phase of the stimulated echo in addition to leading to a position shift of the magnetization amplitude By invoking Fourier transform properties applied to Equation (2), Equation (3) shows that respiratory motion leads to linear and constant phase errors in the k-space domain given by…”
Section: Theorymentioning
confidence: 99%
“…The simulated motion-corrupted data were corrected for linear and constant phase errors (following Equations [3] and [4]) using the known motion, and the resulting k-space data were reconstructed using the nonuniform fast Fourier transform. 18 The motion-corrupted and motion-compensated images were compared with reference images without motion.…”
Section: Bloch-equation Dense Simulations Incorporating Cardiac and R...mentioning
confidence: 99%
See 1 more Smart Citation
“…The heart failure data came from patient studies supported by the American Heart Association, "Personalized Approach to Cardiac Resynchronization Therapy Using High Dimensional Immunophenotyping, " as well as the NIH/NHLBI, "MRI of Mechanical Activation and Scar for Optimal Cardiac Resynchronization Therapy Implementation. " The primary researchers for these studies have reported their results and described their data in the literature [36][37][38].…”
Section: Datamentioning
confidence: 99%